Alignment of project management with business strategy in construction: evidence from the Turkish contractors - Budayan, Cenk; Dikmen, Irem; Birgonul, M. Talat (VILNIUS GEDIMINAS TECH UNIV, 2015)
The importance of fit between an organization's implementation of project management (PM), and its business level strategy is emphasized in the literature. However, there are a limited number of studies investigating the relationship between business level strategy and implementation of PM in the construction industry. This paper aligns one of the business strategies, namely differentiation, with the PM process. A framework representing differentiation in the construction industry is proposed in this study. Structural equation modelling (SEM) is used to validate the relationship between differentiation and the PM process. The results show that a relationship between differentiation strategy and PM exists. The two types of differentiation are revealed, namely product variety and speed-related differentiation (PSD) and quality and image-related differentiation (QID). The companies trying to differentiate based on PSD should focus on cost, time and quality management. Change management and project planning are identified as important drivers of differentiation based on PSD. On the other hand, the companies trying to differentiate on QID should consider health, safety and environmental issues as well as quality. Companies should also manage their resources effectively to support the PM process that in turn leads to successful differentiation. Companies can utilize the research findings as a guideline while formulating their differentiation strategies.
Keywords: competitive advantage; project management; differentiation; strategic alignment; QUALITY MANAGEMENT; FIRM PERFORMANCE; CHANGE ORDERS; INDUSTRY; INITIATIVES; INTEGRATION; OPERATIONS; INNOVATION; FRAMEWORK; SYSTEMS; Engineering